(3caGjI GdeMJGL deYQaI ef djS aj GdOjHGLs - (3CHi GdYHGS CMeO Hf CMeO Hf CMeO Hf YeQ HGHG GdJcQhQi GdJfHcJi GdShOGfi GdeGdcjs; (3GdJfHcJj , CMeO HGHG Hf CMeO Hf CMeO Hf YeQ GdJcQhQj GdShOGfj, CHh GdYHGS,J (B1036 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi fHjI s
(3BNQgG (B:s
(3hBNQ OYhGfG Cf GdMeO ddg QH GdYGdejf s
(3GfXQ Qbe (B" 765"s
(3fSNI KGfjIs
(3hfjd GdGHJgGL Pjdg CHh GdYHGS Ydi cJGH (B" (3GdOjHGL GdePgH ai eYQaI YdeGA GdePgH(B" (3dGHf aQMhfs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs